2008
DOI: 10.1104/pp.108.119917
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Basis and Consequences of a Stay-Green Mutation in thenavel negraCitrus Mutant Using Transcriptomic and Proteomic Profiling and Metabolite Analysis  

Abstract: A Citrus sinensis spontaneous mutant, navel negra (nan), produces fruit with an abnormal brown-colored flavedo during ripening. Analysis of pigment composition in the wild-type and nan flavedo suggested that typical ripening-related chlorophyll (Chl) degradation, but not carotenoid biosynthesis, was impaired in the mutant, identifying nan as a type C stay-green mutant. nan exhibited normal expression of Chl biosynthetic and catabolic genes and chlorophyllase activity but no accumulation of dephytylated Chl com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 108 publications
2
44
0
1
Order By: Relevance
“…Recently, the stay-green (SGR) genes have been cloned from different plant species (Armstead et al, 2006;Barry, McQuinn, Chung, Besuden, & Giovannoni, 2008;Jiang et al, 2007;Park et al, 2007;Sato, Morita, Nishimura, Yamaguchi, & Kusaba, 2007). Further analyses indicate that the expression of SGR is closely associated with leaf senescence and fruit ripening (Alós et al, 2008;Armstead et al, 2006;Barry et al, 2008;Hörten-steiner, 2006;Sato et al, 2007;Yang et al, 2009). Despite the fact that the primary pathway of leaf chlorophyll degradation has been well known, the factors that initiate chlorophyll degradation have still not been understood.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, the stay-green (SGR) genes have been cloned from different plant species (Armstead et al, 2006;Barry, McQuinn, Chung, Besuden, & Giovannoni, 2008;Jiang et al, 2007;Park et al, 2007;Sato, Morita, Nishimura, Yamaguchi, & Kusaba, 2007). Further analyses indicate that the expression of SGR is closely associated with leaf senescence and fruit ripening (Alós et al, 2008;Armstead et al, 2006;Barry et al, 2008;Hörten-steiner, 2006;Sato et al, 2007;Yang et al, 2009). Despite the fact that the primary pathway of leaf chlorophyll degradation has been well known, the factors that initiate chlorophyll degradation have still not been understood.…”
Section: Introductionmentioning
confidence: 96%
“…The latter is commonly employed to investigate expression profiling in many crops. In recent years, several microarray studies involving the Citrus genome have been reported (Shimada et al, 2005;Cerc os et al, 2006;Fujii et al, 2007;Alos et al, 2008). In 2006, Affymetrix developed and released a citrus GeneChip (http://www.affymetrix.com/analysis/ index.affx).…”
Section: Introductionmentioning
confidence: 98%
“…Quantitative real-time RT-PCR was performed with SYBR Premix Ex Taq II kit (Takara) in LightCycler 480 instrument (Roche) equipped with Light-Cycler Software ver. 1.5 (Roche) according to the manufacturer's instructions (Alos et al 2008). All the primers specific for selected peanut genes were designed using the Primer ver.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%